The Influence of Spirituality on Psychological Resilience and Recurrence in Hypertension Patients - Amir, Faisal; Sulistyorini, Lantin; Hasinuddin, M (KHD-Production, 2023)
Hypertension is a chronic disease that is prone to recurrence and disrupts the balance of systemic hemodynamics to cause various serious multi-system complications. This study aimed to analyze the spiritual level in the regulation of resilience and relapse in hypertensive patients. We used a correlation analysis method with a cross-sectional approach. The population was 76 patients who were recorded as coming to the Puskesmas with a sample size of 62 respondents who were taken by simple random sampling. The independent variable was spirituality, as measured using the Daily Spiritual Experience Scale (DSES). The dependent variable was resilience as measured by the Nicholson–McBride Resilience Questionnaire (NMRQ) and hypertension recurrence. Statistical tests using Spearman’s rank with alpha (α) 0.05. The results of the statistical tests show a significant relationship between spirituality and resilience. The p-value obtained is 0.001 less than 0.05, with a level of closeness of 0.790 or solid. Spirituality is also significantly related to hypertension recurrence with a p-value of 0.011, smaller than alpha 0.05, and a level of closeness of -0.325, which means a moderate level of closeness. Deep spirituality will trigger the strengthening of resilience that regulates the balance of stress and homeostasis of the sympathetic and parasympathetic nervous systems. The physiological sympathetic and parasympathetic systems regulate vascular smooth muscle contractions to control blood pressure and reduce the rate of hypertensive recurrence.